NIR-responsive engineered colloidal polyaniline/ZnO/UiO-66-NH₂ nanoplatform: A multifunctional photothermal agent for precision therapy in breast cancer - Shefa Mirani Nezhad; Aboutaleb Kousha; Yasser Rajabi; Ehsan Nazarzadeh Zare; Saeed Rahimi (Alexandria Engineering Journal)
A colloidal polyaniline/ZnO/UiO-66-NH₂ (PANI/ZnO/UiO-66-NH₂) nano-platform was constructed in two steps. The nano-platform exhibited strong optical absorption in the near-infrared (NIR) region, enabling efficient conversion of optical energy into thermal energy under 808-nm laser irradiation, thereby facilitating tumor cell ablation. Characterization was performed using FT-IR, EDX, XRD, FESEM, UV-Vis, and TG. Biological activities, including antioxidant and antibacterial properties, as well as cytotoxicity, were evaluated. The nanocomposite exhibited high photothermal efficiency, reaching 60 °C in 10 min under an 808 nm NIR laser (0.6 W/cm², 1.5 mg/mL), confirming its potential for hyperthermia-based cancer therapy. At 0.15 mg/mL, the temperature rose to 49 °C, demonstrating its concentration and laser power dependence for effective photothermal therapy (PTT). In vitro cytotoxicity analysis on MCF-7 breast cancer cells showed a significant reduction in cell viability under NIR laser irradiation. The MTT assay confirmed that combining the nanocomposite with laser treatment led to a substantial decrease in cancer cell survival, highlighting its potential as a photothermal agent. Additionally, the antioxidant activity of the colloidal PANI/ZnO/UiO-66-NH₂ nanocomposite was found to be 90.64 %, comparable to the highest observed efficiency of UiO-66-NH₂ (94.20 %), and potent antibacterial effects against Escherichia coli (E. coli), Bacillus subtilis (B. subtilis), Salmonella enteritidis (S. enteritidis), and Staphylococcus aureus (S. aureus). Inhibition zone diameters for S. enteritidis and E. coli were 15 ± 0.3 mm and 13 ± 0.1 mm, respectively, underscoring dual applicability in PTT and antibacterial therapy. The MTT assay revealed that colloidal PANI/ZnO/UiO-66-NH₂ reduced the viability of MCF-7 cells to 40 % after 48 h of exposure. The IC₅₀ value of the colloidal PANI/ZnO/UiO-66-NH₂ for inhibiting the growth of MCF-7 cells increased from 17.13 µg/mL after 24 h to 32.3 µg/mL after 48 h. Additionally, hemolysis testing demonstrated that the nano-platform exhibited a hemolysis rate of 5 % at a concentration of 100 μg/mL. These results highlight the nanocomposite’s broad biomedical potential.